(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Recently, the use of co-catalysts has been an important alternative method to improve the visible light photocatalytic activity of pure semiconductor materials. A novel photocatalyst AgBr/BiVO4 was prepared by hydrothermal synthesis and chemical deposition method. The degradation of acid orange 7 was enhanced by AgBr/BiVO4 than pure BiVO4, which was eliminated 92.96% within 80 min under visible light irradiation. It was found that the doping of AgBr could greatly improve the photocatalytic activity of BiVO4 by reducing the recombination of electrons and holes. Prepared photocatalysts were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), UV-vis diffuse reflectance spectra techniques (UV-vis) and X-ray photoelectron spectroscopy (XPS).